Correction: The stability and unexpected chemistry of oxide clusters. Issue 3 (2nd January 2019) - Yu, Xiaohu; Oganov, Artem R.; Zhu, Qiang; Qi, Fei; Qian, Guangrui
Abstract : Correction for 'The stability and unexpected chemistry of oxide clusters' by Xiaohu Yu et al., Phys. Chem. Chem. Phys., 2018, 20, 30437–30444.